Sustainable e-Learning framework: expert views - Mohamed Sofiadin, Aidrina (Springer, 2021)
The efforts toward sustainable development goals in the educational context are of growing importance even in an e-learning perspective. Sustainability aims to improve the e-learning quality since it supports long-term innovation processes while benefiting society, economy, and the environment. In order to portray its prosperous mission, this paper presented the outline of a Sustainable e-Learning Framework (SeLF). This paper aimed to collect the expert perspectives on this framework. Qualitative data were collected through expert interviews during which the utility and usability of the framework were iteratively evaluated and refined. In order to achieve the framework practicability in different contexts, stakeholders from various universities were invited to participate. The expert perceptions and expectations of sustainable e-learning in the context of SeLF were presented in this paper. The experts were asked to reflect on the possible impact of SeLF toward sustainable practices at their own university and personal practice of e-learning sustainability. The findings indicated that SeLF can be used as a guideline for developing sustainable e-learning that supports the continuity of e-learning initiatives.